Enhanced Vulnerability and Capacity Assessments as an organisational learning bridge for resilience building? A case study of Red Cross National Societies in the Caribbean - Delcourt,Gwenaëlle (2023)
Adaptive capacity based on organisational learning (OL) is at once a critical imperative facing humanitarian organisations in their mission to save lives and support communities most at risk; and inherently evidenced as an enduring weakness over the past decades. Vulnerability and Capacity Assessments (VCA) are community-based risk assessments established for their utility in supporting communities’ iterative learning. However, understanding of their potential use for OL remains scarce, owing to their application having been limited to a community-based learning perspective. This timely study sought to explore their potential contribution to OL, specifically investigating the newly released Enhanced Vulnerability and Capacity Assessments (EVCA) of the IFRC as the methodology in real-time. A multi-case study approach involved 4 National Societies in the Caribbean region with whom 17 interviews were conducted, alongside 6 interviews with HQ-level informants and document analysis complementing the empirical data. Results revealed a significant potential for the Enhanced VCA methodology to contribute to learning at the micro, meso and macro levels, contingent upon leveraging a nexus of motives, means, and opportunities for OL. The study provides additional evidence to previous studies having nuanced enduring gaps in leveraging assessment processes for learning by further nuancing the interactions and systemic interdependences at play. Notwithstanding its contextual scope specifically focused on the IFRC and Caribbean region, the study provides insight which could be of interest in other contexts.
Keywords: Organisational learning; resilience; vulnerability and capacity assessments (VCAs); red cross red crescent; Disaster risk management; MMO